Proof: Compare Example Three
Let's prove the following theorem:
compare bit stack [ 1, [ 0, [ 1, [ ] ] ] ] and bit stack [ 0, [ 1, [ 1, [ ] ] ] ] = [ 0, [ 0, [ ] ] ]
Proof:
# | Claim | Reason |
---|---|---|
1 | compare bit stack [ 0, [ 1, [ ] ] ] and bit stack [ 1, [ 1, [ ] ] ] = [ 0, [ 0, [ ] ] ] | compare bit stack [ 0, [ 1, [ ] ] ] and bit stack [ 1, [ 1, [ ] ] ] = [ 0, [ 0, [ ] ] ] |
2 | compare bit stack [ 1, [ 0, [ 1, [ ] ] ] ] and bit stack [ 0, [ 1, [ 1, [ ] ] ] ] = [ 0, [ 0, [ ] ] ] | if compare bit stack [ 0, [ 1, [ ] ] ] and bit stack [ 1, [ 1, [ ] ] ] = [ 0, [ 0, [ ] ] ], then compare bit stack [ 1, [ 0, [ 1, [ ] ] ] ] and bit stack [ 0, [ 1, [ 1, [ ] ] ] ] = [ 0, [ 0, [ ] ] ] |
Comments
Please log in to add comments